2017
DOI: 10.1093/schbul/sbx091
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Hyperconnectivity in the Motor System at Rest Is Linked to Motor Abnormalities in Schizophrenia Spectrum Disorders

Abstract: Motor abnormalities are frequently observed in schizophrenia and structural alterations of the motor system have been reported. The association of aberrant motor network function, however, has not been tested. We hypothesized that abnormal functional connectivity would be related to the degree of motor abnormalities in schizophrenia. In 90 subjects (46 patients) we obtained resting stated functional magnetic resonance imaging (fMRI) for 8 minutes 40 seconds at 3T. Participants further completed a motor battery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 119 publications
(88 citation statements)
references
References 84 publications
10
78
0
Order By: Relevance
“…In particular, the observed hypokinesia, i.e., reduction of motor activity, is associated with an aberrant coupling of cortical and subcortical motor areas. This association has been corroborated by data on gray matter density, gray matter perfusion, and WM properties [63, 121]. …”
Section: Mapping Symptoms Onto Brain Systems: Empirical Evidence For mentioning
confidence: 60%
“…In particular, the observed hypokinesia, i.e., reduction of motor activity, is associated with an aberrant coupling of cortical and subcortical motor areas. This association has been corroborated by data on gray matter density, gray matter perfusion, and WM properties [63, 121]. …”
Section: Mapping Symptoms Onto Brain Systems: Empirical Evidence For mentioning
confidence: 60%
“…Aberrant top-down effects from PFC on motor-related cortical and sub-cortical regions has been suggested to contribute to symptoms of schizophrenia(27,58). For example, catatonic patients not only exhibited prefrontal hypoactivation and frontal gray matter loss(17,59), but also had altered connections between PFC and premotor/motor cortex(60). In a recent study of Walther and colleagues, catatonia was associated with higher perfusion in supplementary motor area and prominent GM loss in frontal and insular cortices(61), which resemble the SICI-related PFC and insula clusters observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the literature. The cerebellar-motor circuit is linked to deficit of sensorimotor control in schizophrenia(17,61,82) and stimulation of cerebellum altered the size of SICI at motor cortex(83); and the involvement of cerebellum in the neuropathology of schizophrenia is well supported(82,84). However, it should be noted that the association between SICI and cerebellum did not pass LOOCV test and this finding need to be confirmed by future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have identified reduced volumes of the primary and secondary motor cortex in SCZ patients (Douaud et al 2007; Wang et al 2018). Furthermore, altered neuronal activity in the area was related to negative symptom of SCZ (Walther et al 2017), suggesting that motor cortex may play a role in SCZ pathogenesis. Although it is difficult to examine whether or how the AQP3 gene confers a risk for SCZ, abnormal AQP3 expression may contribute to dysregulated motor network in SCZ.…”
Section: Discussionmentioning
confidence: 99%